Efek Pemberian Tepung Kunyit Pada Kondisi Hematologis Burung Puyuh (Coturnix coturnix japonica L) Saat Masa Produktif Dan Non produktif - Rahayu, Catur; Isroli, Isroli; Saraswati, Tyas Rini (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Productivity of livestock with chemical additives becoming obsolete, now developed, from natural herbal additives such as turmeric contains curcumin is efficacious as antihepatotoksik enthelmintik, antiedemik, analgesic, anti-inflammatory and antioxidant and effective fat metabolism in the body. The purpose of this study was to determine the effect of turmeric powder as a feed supplement in feed quail with different delivery periods to optimize tissue function in order to carry out metabolism and maintain the physiological functions of tissues seen from the number of erythrocytes and hemoglobin levels. This study used 30 female quails (Cortunix cortunix japonica) in similar age groups divided into 3 treatment groups namely P0 (not given turmeric), P1 (group fed turmeric as non productive age the age of 210 days) and P2 (group turmeric was given before the age of non-productive until age 14 -240 days). Quail were decapitated at the age of 240 days and taken blood in tubes containing EDTA venojack. Examination of the number of erythrocytes and hemoglobin using a counting chamber method and the method of Sahli done on the same day to ensure the validity of data. Research results showed that administration of turmeric in non-productive age (age 210 days) could potentially increase the amount of hemoglobin and the number of erythrocytes (P <0.05), compared with quail fed turmeric since 14 days and control treatments. The average number of erythrocytes P0, P1, and P2, respectively 3,285; 4.7; 2,729 and Mean hemoglobin levels P0, P1, and P2, respectively 12.27; 15.0; 13.5. It is concluded that administration of turmeric in the non produktrif potentially increase cell metabolism is marked by an increase in the number of erythrocytes and hemoglobin count.